Atypical Presentation of Gallstone Ileus: A Case Report - Santos, Emilly Hanay Mori; Terasoto, Lucas; Barbosa, Natalia Elena Trentiny; Stier, Sarah Alícia Garcia; Miranda, Alyne Sousa; Terasoto, Renan de Pizza; Ferreira, Raphael Machado de Sá (Brazilian Journal of Case Reports, 2026)
Gallstone ileus is a rare complication of cholelithiasis, resulting from the impaction of an ectopic gallstone within the gastrointestinal tract, leading to intestinal obstruction. Its clinical presentation is variable, with abdominal pain associated with obstructive symptoms being the most common presentation. In this report, we describe the case of a patient with an atypical presentation of gallstone ileus, with diarrhea as the initial manifestation and no evident signs of intestinal obstruction, who underwent laparoscopic surgical treatment for removal of the ectopic stone, followed by outpatient management of cholelithiasis.